Efficacy of uterotone in induction of uterine contraction in vitro and expulsion of fetal membranes in buffaloes - GAUTAM, R P; TIWARI, R P; KOLEY, K M (The Indian Journal of Animal Sciences, 2014)
Efficacy of uterotone was evaluated in inducing uterine contraction in vitro. prevention of retention of fetal membranes(RFM) and treatment of RFM in buffaloes. In experiment 1, pieces of estrus goat uterus obtained tram slaughter house were exposed to utrotone liquid in organ bath with continuous airation. A tension of 1 g weight was put to the tissues to record tissue contraction on chymograph. In experiment 2, uterotone liquid was administered in buffaloes after calving to observe the effect of uterotone therapy on expulsion of fetal membranes and reproductive performance. In experiment 3. utero tone therapy was given in buffaloes for the treatment of retained fetal membranes. Experiment 1, indicated dose dependent induction of uterine contraction by uterotonc. Experiment 2 showed the significantly carly expulsion Df fetal membranes(5.29Â± 0.48 Vs 7.33. Â± 0.74 hr, P